Potret implementasi CSR dalam konteks laporan keberlanjutan: Studi kasus PT Vale Indonesia di Sorowako - St. Nur’ Azizah Tompunu; Azizah Tompunu (Journal of Economics Research and Policy Studies, 2025)
This study examines the gap between sustainability narratives in PT Vale Indonesia’s 2024 Sustainability Report and the socio-environmental realities surrounding its CSR practices in Sorowako, Indonesia. The research employs a descriptive qualitative approach based on document study, comparing the company’s report with documents from civil society organizations. Legitimacy theory and stakeholder theory frame the analysis to interpret how the sustainability image is constructed and how stakeholder expectations are addressed. Findings reveal three key gaps: limited and non-representative community participation, minimal disclosure of unresolved ongoing environmental impacts, and CSR programs predominantly oriented toward activities rather than long-term socio-economic benefits for local communities. The results indicate that the company’s sustainability reporting remains largely affirmative and procedural, while external documents emphasize persistent ecological risks and unmet public expectations. This study recommends enhanced transparency of mining impact disclosures, broader and inclusive community engagement in CSR evaluation, and periodic independent assessments of sustainability outcomes.